The accuracy of ultrasound guided technique for lumbar intervertebral disc level localisation - Chia Sing, Wong (2015)
Introduction and objective Spinal level localisation is a very important factor in any spine surgery to ensure that the operation is performed at the correct site. C-arm image intensifier is the current practice in operating theatre for most of the spinal surgery. However, its use is related to a few problems. Ultrasound can be a good alternative. Ultrasound guided technique has gain popularity for spinal procedure especially among anaesthetist and rheumatologist. Study design and methodology This was a cross-sectional study of 80 participant equally divided into normal spine group and degenerative spine group. Ultrasound guided intervertebral disc localisation of L3/L4, L4/L5 and L5/S1 was performed on all participant in prone position by a single operator. A standardised steps were used and inferior edge of spinolaminar junction of the overlying vertebral was used as a sonographic landmark representing a particular disc level. A radiopaque marker was placed on each disc level identified for accuracy checking using X-ray machine or C-arm image intensifier. Radiopaque marker crossing at least 50% of the width of the intended intervertebral disc was defined as accurate. Result Pertinent landmark for intervertebral disc localisation were identified with ultrasound guidance in all participants with overall accuracy rate of 65.0%. No significant different in accuracy localising L3/L4 disc in normal spine (32.5%) and degenerative spine (40.0%) group. However accuracy was significantly higher in normal group (82.5%) compared to degenerative group (60.0%) at L4/L5 disc level. We had higher accuracy localising L5/S1 disc in both groups with same accuracy of 87.5%. Conclusion Ultrasound guidance intervertebral disc localisation is a feasible approach to localise lumbar discs using spinolaminar junction of overlying vertebra as a landmark. It can be safely performed at L5/S1 disc level in patient with or without degenerative spine disease. It can also be considered in patients without degenerative spine disease at L4/L5 disc level. However it is not recommended to localise L3/L4 disc level. Keywords : Lumbar, intervertebral disc, disc level localisation, ultrasound, sonoanatomy